P300 in individuals with sensorineural hearing loss - Reis,Ana Cláudia Mirandola Barbosa (2015)
INTRODUCTION: Behavioral and electrophysiological auditory evaluations contribute to the understanding of the auditory system and of the process of intervention.OBJECTIVE: To study P300 in subjects with severe or profound sensorineural hearing loss.METHODS: This was a descriptive cross-sectional prospective study. It included 29 individuals of both genders with severe or profound sensorineural hearing loss without other type of disorders, aged 11 to 42 years; all were assessed by behavioral audiological evaluation and auditory evoked potentials.RESULTS: A recording of the P3 wave was obtained in 17 individuals, with a mean latency of 326.97 ms and mean amplitude of 3.76 V. There were significant differences in latency in relation to age and in amplitude according to degree of hearing loss. There was a statistically significant association of the P300 results with the degrees of hearing loss (p = 0.04), with the predominant auditory communication channels (p < 0.0001), and with time of hearing loss.CONCLUSIONS: P300 can be recorded in individuals with severe and profound congenital sensorineural hearing loss; it may contribute to the understanding of cortical development and is a good predictor of the early intervention outcome.